Highly Efficient and Solution‐Processed Single‐Emissive‐Layer Hybrid White Organic Light‐Emitting Diodes with Tris(triazolo)triazine‐Based Blue Thermally Activated Delayed Fluorescence Emitter. Issue 24 (6th October 2021) - Chen, Xinrui; Wang, Shengyue; Lee, Ha Lim; Lee, Jun Yeob; Liao, Xiaoqing; Li, Lu; Zhu, Weiguo; Wang, Yafei
Abstract: Solution processable organic light‐emitting diodes (OLEDs) based on thermally activated delayed fluorescence (TADF) emitters show inferior efficiency to devices produced via vacuum deposition. In this context, solution‐processed hybrid white OLEDs are fabricated using a TADF molecule and iridium complex as the blue and red dopants, respectively. First, solution‐processed OLEDs employing a tristriazolotriazine‐based TADF as the blue dopant are designed and fabricated, yielding maximum external quantum efficiency (EQEmax ) of 23.23% with an emission peak at 492 nm. Use of the optimized tristriazolotriazine‐based TADF OLED structure and additional red phosphor achieves highly efficient white light emission with an EQEmax of 22.57%, stable Commission International de l'Eclairage (CIE) coordinates of (0.34, 0.34), a correlated color temperature of 5000 K, and a color rendering index of 73. Impressively, accelerated lifetime testing shows the white OLED possessing a lifetime to 80% of initial luminance (LT80) of 40 h, and an LT50 of 298 h. To the best of knowledge, the device performance demonstrated in this work is one of the best comprised of solution‐processed blue and fluorescent‐phosphorescent hybrid white OLEDs. This research provides a reliable method for high efficiency solution processable blue TADF and TADF‐phosphorescent hybrid OLEDs. Abstract : Solution‐processed hybrid white organic light‐emitting diodes are fabricated using a tristriazolotriazine‐based thermally activated delayed fluorescence molecule and iridium complex as the blue and red dopants, respectively, which show a maximum external quantum efficiency (EQEmax ) of 22.57%, stable Commission International de l'Eclairage coordinates of (0.34, 0.34), a correlated color temperature of 5000 K, and a color rendering index of 73.